2009
DOI: 10.1016/j.cellbi.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cancer effect ofCassia auriculataleaf extractin vitrothrough cell cycle arrest and induction of apoptosis in human breast and larynx cancer cell lines

Abstract: The in vitro anti-cancer effect of Cassia auriculata leaf extract (CALE) was evaluated in human breast adenocarcinoma MCF-7 and human larynx carcinoma Hep-2 cell lines. CALE preferentially inhibited the growth of both the cell lines in a dose-dependent manner with IC(50) values of 400 and 500 microg for MCF-7 and Hep-2 cells, respectively. The results showed the anti-cancer action is due to nuclear fragmentation and condensation, associated with the appearance of A(0) peak in cell cycle analysis that is indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Metabolically active cells are able to convert the dye to water-insoluble dark blue formazan by reductive cleavage of the tetrazolium ring. The reduction of MTT is proportional to the number of active mitochondria in the live cells (Prasanna et al, 2009). From the present study the % of inhibition was reduced in D-pinitol treated cells.…”
Section: Resultsmentioning
confidence: 64%
“…Metabolically active cells are able to convert the dye to water-insoluble dark blue formazan by reductive cleavage of the tetrazolium ring. The reduction of MTT is proportional to the number of active mitochondria in the live cells (Prasanna et al, 2009). From the present study the % of inhibition was reduced in D-pinitol treated cells.…”
Section: Resultsmentioning
confidence: 64%
“…We observed upregulation of FasL, caspase-8 and caspase-3 expression upon curcumin and BDMC-A treatment, and found that this upregulation was more pronounced in BDMC-A treated cells, indicating its more potent ability to activate the extrinsic apoptotic pathway. We also found that BDMC-A treated Hep-2 cells showed nuclear fragmentation, which is another prominent feature of apoptosis [43], and that this nuclear fragmentation was more pronounced in BDMC-A treated cells compared to curcumin treated cells.…”
Section: Discussionmentioning
confidence: 88%
“…Previous reports demonstrate the antiplasmodial (Kamaraj et al, 2011) anti-diabetic (Gupta et al, 2010), larvicidal ) and anti-cancer (Prasanna et al, 2009) effects of leaf extracts of Cassia auriculata. Juan-Badaturuge et al (2011) isolated the antioxidant kaempferol-3-O-rutinoside, kaempferol, quercetin and luteolin from Cassia auriculata.…”
Section: Discussionmentioning
confidence: 97%